Robot voice control grammars development - Андрусевич, Анатолий Александрович; Милютина, Светлана Святославовна; Невлюдова, Виктория Валерьевна (Eastern-European Journal of Enterprise Technologies, 2014)
Application of industrial robots can improve the production flexibility. However, in this case, there is a need to write control programs. Herewith, we should maximize the facilitation of this process, the introduction of voice control can be one of these ways. The basic principles of forming robot control grammars are presented. The feasibility of developing the proposed grammars is explained by the need to formalize the industrial robot control language, which is close to natural. The sequence of actions that allows implementing the voice control was developed. The key (pre-control) words and allowable sequences of voice command input were defined. The basic characteristics of the RM-01 robot, as well as the movement restrictions were considered. The basic methods and properties, implemented by the program are given. The XML-file, containing the library of robot control words, its structure and principles of creation, were considered. Thus, the developed library provides the possibility of its expansion for adapting to other models of industrial robots.